The ecology, biogeography and speciation of the butterflies of the Azores, by Mark Payne. Hardback. World Natural History Publications, “The Lake District”, 2019, 370 pp. - Tennent, John (2021)
This is the second book in a planned series of numerous books covering all of the world’s butterflies. It opens with a detailed and lengthy account of the author, his supposed achievements and future plans. A prominent acknowledgement to Martin Wiemers, a highly respected European entomologist, is out of date. Martin has disassociated himself from the books and withdrawn co-authorship of a proposed volume on Macaronesian endemic butterflies advertised in the book. […].